Total knee replacement: intraoperative and postoperative kinematic assessment - Bontempi, M.; Cardinale, U.; Bragonzoni, L.; Macchiarola, L.; Grassi, A.; Signorelli, C.; Marcheggiani Muccioli, G. M.; Zaffagnini, Stefano (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: The main goals of the total knee arthroplasty (TKA) is to reduce the perceived pain and  restore knee mobility and function in case of osteoarthritic knees joints. Literature shows how the three major causes of TKA failures are related to wear, loosening and instability and this is due to a problem of imbalance and malalignment. Intraoperative and postoperative kinematics analysis could be of benefit for improving surgery outcome. The aim of the present paper is to give an overview of the two set-up with the highest accuracy for intraoperative and postoperative TKA kinematics evaluation, currently in use at Istituto Ortopedico Rizzoli. Introperative and Postoperative Evaluation: For intraoperative evaluation it has been presented a navigation system with a specifically developed software, while for the postoperative it has been presented the roentgen stereophotogrammetric analysis (RSA). The navigation system consists in a laptop connected with an optoelectronic localizer (Polaris, Northern Digital Inc, Canada).  Two reference arrays with passive optical markers and a marked probe are used to localize the knee joint in the 3D space and track the joint kinematics. The RSA is a radiographic technique used in orthopaedic field for measuring micromotion at bone/prosthesis interface or for joint kinematics evaluation. The RSA uses two X-ray sources synchronized with two digital flat-panels. Conclusions: The present paper shows that using the navigation system allows the surgeon to easily perform kinematic and alignment evaluation during TKA surgery while the RSA allows a quantitative evaluation of the joint kinematics during the recovery time.